Olof Lagercrantzin lyriikan kehityslinjat : runoanalyyseja - Littunen, Teuvo (1997)
This dissertation concerns the poems of Olof Lagercrantz published in book-form. His four collections are Den döda fågeln (The dead bird, 1935), Den enda sommaren (The only summer, 1937), Dikter från mossen (Poems from the swamp, 1943) and Linjer (Lines, 1962). In the case of some poems I also make use of the last version published in En blödande ros (A bleeding rose, 1991), the latest collection of selected poems, including poems that have not earlier been published in book-form. Outside Sweden, Lagercrantz (born 10.3.1911) is best known as the writer of books such as August Strindberg (1979), Min första krets (My first sphere, 1982), Från helvetet till paradiset (From hell to paradise, 1964) and Om konsten att läsa och skriva (On the skill of reading and writing, 1986) - as well as the editor-in-chief of Dagens Nyheter (1960-75). In this study these works together with biographical knowledge of Lagercrantz serve as subtexts for the poems. Other literary subtexts are the works of E.A. Karlfeldt, Karin Boye and Dante as well as the Bible and other well-known books that have reference to the poems of Lagercrantz. My study primarily takes the form of a structural and comparative analysis with the aim of investigating changes in the style and the attitude of Lagercrantz's poems. I also attempt to form a general image of Lagercrantz's production as a whole. Lagercrantz could be summed up as a poet of freedom and spiritual liberation. A comparison of Lagercrantz's poems from 1930s, 1940s and 1960s reveals a trend towards the renouncing of rhyme, a seeking of new metaphors and a more aggressive manifestation of opinions and feelings. The last collection of poems (1962) contains criticism of our hypocrisy and artificiality - in place of the descriptions of nature and birds which are central in the first two collections. The third collection with its elegies already shows signs of the coming radicalism of the later Lagercrantz. The poems have, besides gaining more flexible also become more openly critical of western society.